Public support for censorship in a highly regulated media environment: The influence of self-construal and third-person perception over time - DETENBER, Benjamin H. (Institutional Knowledge at Singapore Management University, 2018)
This study represents the first longitudinal examination of third-person effects and uses a rigorous specification of the relative contribution of perceptions of influence on self and others (viz., the diamond method). Using nationally representative samples from Singapore gathered in 2001 (n = 626) and 2013 (n = 1,012), it examines perceptions of sex and nudity in films, content that the government allows but regulates. As expected, interdependent self-construal and third-person perceptions predicted support for censorship, as did perceived total media influence. The pattern of prediction was quite consistent with a slight increase in support for censorship. The discussion considers implications with respect to both the social landscape and an evolving media landscape.